Tumor-associated stromal cells as key contributors to the tumor microenvironment - Bussard, Karen M. (Breast Cancer Res, 2016)
The tumor microenvironment is a heterogeneous population of cells consisting of the tumor bulk plus supporting cells. It is becoming increasingly evident that these supporting cells are recruited by cancer cells from nearby endogenous host stroma and promote events such as tumor angiogenesis, proliferation, invasion, and metastasis, as well as mediate mechanisms of therapeutic resistance. In addition, recruited stromal cells range in type and include vascular endothelial cells, pericytes, adipocytes, fibroblasts, and bone-marrow mesenchymal stromal cells. During normal wound healing and inflammatory processes, local stromal cells change their phenotype to become that of reactive stroma. Under certain conditions, however, tumor cells can co-opt these reactive stromal cells and further transition them into tumor-associated stromal cells (TASCs). These TASCs express higher levels of proteins, including alpha-smooth muscle actin, fibroblast activating protein, and matrix metalloproteinases, compared with their normal, non-reactive counterparts. TASCs are also known to secrete many pro-tumorigenic factors, including IL-6, IL-8, stromal-derived factor-1 alpha, vascular endothelial growth factor, tenascin-C, and matrix metalloproteinases, among others, which recruit additional tumor and pro-tumorigenic cells to the developing microenvironment. Here, we review the current literature pertaining to the origins of recruited host stroma, contributions toward tumor progression, tumor-associated stromal cells, and mechanisms of crosstalk between endogenous host stroma and tumor cells.